RETRACTED ATICLE: Physcion 8-O-β-glucopyranoside exerts protective roles in high glucose-induced diabetic retinopathy via regulating lncRNA NORAD/miR-125/STAT3 signalling - Wencui Wan; Weiwei Wan; Yang Long; Qiuming Li; Xuemin Jin; Guangming Wan; Fengyan Zhang; Yong Lv (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Wencui Wan, Weiwei Wan, Yang Long, Qiuming Li, Xuemin Jin, Guangming Wan, Fengyan Zhang & Yong Lv. (2020). Physcion 8-O-β-glucopyranoside exerts protective roles in high glucose-induced diabetic retinopathy via regulating lncRNA NORAD/miR-125/STAT3 signalling. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 463–472, DOI: 10.1080/21691401.2019.1709861Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors associated with the figures presented. In addition, the corresponding author of the article, Qiuming, has informed us they were not aware of the submission made under their name. The authors have agreed to the retraction of this article, and we have also informed the institution about the authorship issues related to this article.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.